Penerapan Konsep Fisika pada Greenhouse Berbasis Control Iklim: Studi Literatur - Sari, Sindi Novita; Liana, Nur; Mahmudi, Kendid; Sudarti, Sudarti (Journal of Health, Education, Economics, Science, and Technology, 2025)
The increasing pressures caused by climate change and global population growth are driving the need for innovation in the agricultural sector to ensure sustainable food security. Greenhouses represent one solution as they can create a controlled microenvironment to support optimal plant growth. This study discusses the application of physical principles in climate control systems in greenhouses integrated with Internet of Things (IoT) technology, using a systematic literature analysis approach. Various physics concepts, such as heat transfer mechanisms, thermodynamics, fluid flow, and light intensity measurement, are applied to regulate environmental parameters such as temperature, humidity, and lighting efficiently. Technology support in the form of sensors, actuators, microcontrollers, and intelligent algorithms enables the process to occur automatically and responsively. The results show that the application of physics in the design and operation of greenhouses can improve energy efficiency, agricultural productivity, and promote sustainable precision agriculture. This agro-physics-based approach serves as an important foundation for the future development of smart greenhouse systems.